KEPEMIMPINAN TRANSFORMASIONAL DAN EFIKASI DIRI SEBAGAI PREDIKTOR WORK ENGAGEMENT KARYAWAN - , PITASARI IRMA TRISYANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Work engagement is an essential contributor in efforts of avoiding high rate of employee turnover, maintaining customersâ satisfaction and achieving optimum performance of an organization. In order to succeed, a company needs to have a good strategy in promoting engagement of its employees to prevent losing its most valuable employees. Propagation of employeesâ work engagement is closely related to the leadership style of company leaders in encouraging extra-efforts and promoting job satisfaction towards their employees. Recent research have shown that transformational leadership could increase employeesâ motivation and satisfaction in doing their job. Not only the employees are satisfied, they will also feel proud and content with their job. Self efficacy refers to individual confidence on their ability to succeed in a particular job. Selfefficacy can be a motivational factor which influences employeesâ work engagement.This research aims to study whether transformational leadership and self-efficacy are predictors of employeesâ work engagement. The hypothesis suggests that transformational leadership and self-efficacy can be used as predictors for employeesâ work engagement. Subjects in this research are full time employees of a company who have a minimum of one year of service. This research is a fieldwork study using quantitative methods and employs questionnaire as a data collection method. Conducting a multiple regression analysis on 110 respondents, the result shows that both transformational leadership and self-efficacy variables significantly predicts employeesâ work engagement (F=36,799, p < 0.05) with a contribution of 40.8%.